Simulation of Interprofessional Collaboration on Self-Awareness of Diabetes Mellitus Patients - Muhammad Sajidin; Arief Andriyanto (STIKes Patria Husada Blitar, 2024)
Diabetes mellitus is a non-communicable disease that is included in the chronic disease category and is expected to increase, so a method is needed to carry out the control recommended by the Ministry of Health in the form of intelligent management of diabetes mellitus. The management given to people with diabetes is developed based on the theory of the Health Promotion Model and the form of Diabetes Self-Management Education (DSME) intervention. The aim was to analyze the simulation of interprofessional collaboration on self-awareness of diabetes mellitus patients. Quasi Experiment Pre-Post Test with Control Group Design for 4 weeks consisting of 8 sessions and each session + 30 minutes. The samples were taken using simple random sampling technique, namely type 2 diabetes mellitus as many as 58 respondents in each intervention and control group. The instrument used a diabetes mellitus self-awareness questionnaire with 51 statement items that had been tested for validity and reliability. The data analysis used a paired t-test. There was a significant difference in the self-awareness of people with type 2 diabetes before and after being given the Interprofessional Collaboration Simulation (IPC-S) which had a significant p-value of 0.001 <0.05. In the control group, there was no significant difference in the self-awareness of people with type 2 diabetes before and after being given Interprofessional Collaborative Simulation (IPC-S) with a significant p-value of 0.569 > 0.05. There was a difference in self-awareness in the intervention group because the method provided was complete which was adapted to the needs of the patient so far, to still be able to manage the disease so that blood sugar levels can be controlled. This activity directly has also made the respondents in the intervention group have more self-awareness, higher than the control group.